Back Cover Image. (25th November 2021) - Chen, Haifei; Zhang, Quan; Wang, Xueru; Zhang, Jianhua; Ismail, Abdelbagi M.; Zhang, Zhenhua
Abstract : The cover image is based on the Original Article Nitrogen form‐mediated ethylene signal regulates root‐to‐shoot K + translocation via NRT1.5 by Haifei Chen et al., https://doi.org/10.1111/pce.14182 .